If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 1 = 26 Reorder the terms: 1 + X = 26 Solving 1 + X = 26 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + X = 26 + -1 Combine like terms: 1 + -1 = 0 0 + X = 26 + -1 X = 26 + -1 Combine like terms: 26 + -1 = 25 X = 25 Simplifying X = 25
| -12=-2c+22 | | 13x+31y=388 | | 16-20/2+(-8)/2.2-4.0= | | -1y=-2y-9 | | 3(a-5)+4a-6=0 | | 4(2y-6)=78+2y | | -3g+8=-4+3-4g | | -3g+8=-4+3--4g | | (x-1)(x+1)(x+3)=315 | | 2-m=6 | | 18x-6=35+14x | | y=1x(2x^2) | | 2x^2+14x=7x+4 | | 6+a=-4a-9 | | 6w+5-2w=25 | | y=-k^2+4k+6 | | p-1=5p-1+3p-8 | | 16d+29d+13d=200 | | 9-9x=12x+6 | | 14-2y+5=-2y+9 | | 24-6k=-2(-2+5k) | | 20x^2-48x-36=0 | | -24x-6=3x+27 | | 24-6k=2(-2+5k) | | -5(11-3x)=15 | | 6x(x+3)=30 | | -4+2y=-30 | | -9n+7=-10n | | 80=2(8+a) | | 3(175x+152)= | | 10.5+0.5p=0.9p+5.3 | | 14-(2y+5)=-2y+9 |